Politik Hukum Penguatan Kewenangan DSN-MUI dalam Sistem Hukum Ekonomi Nasional - Baiquni, Aryo Purboyo Wisnuwardhana; Maksum, Muhammad; Nurhasanah, Nurhasanah (Law, Development and Justice Review, 2026)
Normatively, DSN-MUI fatwas serve as the primary guideline for the operation of Islamic financial institutions. However, in formal juridical terms, those fatwas do not yet have binding legal force because they are not included in the hierarchy of statutory regulations. As a result, the authority of the Sharia supervisory body is positioned below the state’s legal authority, leading to a dualism of powers between DSN-MUI, the Financial Services Authority (OJK), and Bank Indonesia. The impact of that legal uncertainty affects actors in the Islamic economic sector and indicates that legal politics have not fully integrated Islamic law substantively. The problems in this study will be addressed by examining the position of DSN-MUI and the fatwas produced by DSN-MUI within the national economic law system through the lens of legal politics. The main aims of this research are to analyze the institutional position and fatwas of DSN-MUI; to identify obstacles that hinder the strengthening of DSN-MUI’s authority; and to offer legal-political recommendations to bolster DSN-MUI’s role within the national economic legal system. This research is expected to contribute to the literature on Islamic economic law and to provide clearer policy direction for regulators and stakeholders in Indonesia’s Islamic finance industry. The study is qualitative, using a normative juridical method with legislative and conceptual approaches. The results show that the legal politics of Islamic economics in Indonesia remain limitedly accommodative by allowing space for Sharia values, whereby DSN-MUI fatwas which are DSN-MUI’s legal products continue to serve as a normative basis for OJK and BI in regulatory formation also as a foundational guideline for Islamic finance industry actors in conducting their practices. However, the non-binding juridical status of DSN-MUI fatwas indicates that DSN-MUI has not been granted adequate sovereignty.